Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Largemouth bass virus infection subverts immune-redox homeostasis in zebrafish and is associated with coordinated suppression of NF-κB and Nrf2 signaling - Lingfeng Guan; Xinyue Zhang; Ting Yu; Yang Liu; Jiamei Long; Runchang Zhou; Hua Huang; Jinglin Tan; Zhifeng Chen; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2026)

Multi-objective optimization of ship resistance and seakeeping using an improved Voronoi-based parallel sequential sampling method - Dongqin Li; Yu Zhang; Yanqing Yin; Wenwen Chen; Bohan Wang; Zishuai Wang; Lingfeng Lu (Ocean Engineering, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

Interdigitated electric-magnetic gradient MXene-based nanocomposite films for concurrent high-efficiency electromagnetic shielding and sensitive detection - Lingfeng Yu; Yanni Yang; Shulong Chang; Yihao Xiao; Song Luo; Shichun Hao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Granular hydrogel gradient microenvironments drive functional osteochondral interface regeneration - Jing Wang; Wenbo Zhong; Chengxiang Sha; Yu Shen; Zhaowei Yin; Lingfeng Yuan; Bin Liang; Xi Zeng; Jing Zhang; Ziyi Yu (Chemical Engineering Journal, 2026)

Modelling and operation performance of the hybrid borehole heat exchangers constituted of a shallow U-pipe array and medium-deep coaxial pipe - Shilong Yang; Yaru Li; Lingfeng Huang; Qingbo Yang; Ke Zhu; Yudong Mao; Wenke Zhang; Mingzhi Yu (Energy and Buildings, 2026)

Dietary 5-aminolevulinic acid induces strain-specific effects on shell color and innate immunity in Pacific oyster (Crassostrea gigas) through divergent porphyrin metabolism - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Fish & Shellfish Immunology, 2026)

Nickel incorporation engineering for synergistic regulation of oxygen vacancies and electronic band configuration in Bi2O3 nanosheets for high-performance supercapacitor electrodes - Lingfeng Li; Weihao Zhang; Xuexuan Luo; Xueyi Chang; Muqing Chen; Zhiyu Cheng; Yongfu Qiu; Yu Wang (Chemical Engineering Journal, 2026)

Potential predictability of global seasonal precipitation anomalies determined by climate modes - Yu Wang; Xiu-Qun Yang; Dejian Yang; Lingfeng Tao; Jiabei Fang; Xuguang Sun (Climate Dynamics, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Multiscale-reinforced high-strength MXene-based EMI shielding films with integrated electronic skin functionalities - Lingfeng Yu; Yanni Yang; Xinyu Huang; Yihao Xiao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Comparative Analysis Provides Insights into the Phylogeny of Chamidae (Bivalvia: Veneroida) Through a Mitogenomic Approach - Jing Li; Yu Wang; Tao Xu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2026)

Reproductive capacity and hereditary impact of triploid Crassostrea gigas and its aneuploid progeny - Xianchao Bai; Hong Hu; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Haijun Liu; Shaojun Du; Qi Li (Marine Life Science & Technology, 2026)

Orange-shell phenotype regulated by CgABCG2-mediated protoporphyrin IX transport in Pacific oyster (Crassostrea gigas) - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Aquaculture, 2026)

Effects of cold plasma treatment and xanthan gum on the longan seed starch: physicochemical, rheological and digestive properties - Rui Huang; Yitong Chen; Lingfeng Cheng; Mengzhu Shen; Yaqin Yu; Fangfang Wu; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2025)

Nanomaterial-powered immunotherapy: A next-generation therapeutic paradigm for bacterial infections - Xiaotong Sun; Shengnan Huang; Tong Ye; Lingfeng Xu; Yongfang Wang; Anqi Liu; Chao Liu; Yu Han; Mengfei Pang; Xuan Wu; Xin Pang (Chemical Engineering Journal, 2025)

Devonian–Triassic tectonic evolution of the Western Qinling Orogenic Belt of central China: Insights from detrital zircon U Pb chronology and rock geochemistry - Yan Zhang; Shuang Dai; Futian Liu; Dongbao Guo; Lingfeng Qin; Zhongzhao Ding; Yongfa Chen; Xinnan Fang; Xiaojun Ma; Yu Wang; Hua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Critical hydro-geomorphological characteristics related to lateral erosion–deposition difference within the multilevel bifurcation system of the Yangtze Estuary, China - Boyuan Zhu; Shiyu Zhang; Lingling Zhu; Lingfeng Liu; Wenjun Yu; Jinwu Tang; Yongzhou Cheng; Yitian Li; Alistair G.L. Borthwick (Journal of Hydrology, 2025)

Biosynthesis of ag nanoparticles by aqueous extracts from soybean pods and tea residues: enhanced antioxidant and antibacterial activity - Chun Song; Lingfeng Wang; Hanghang Yu; Yu Wang (Nanotechnology for Environmental Engineering, 2025)

In-situ atmospheric thermoelectric conversion on Mars - Yuzhuo Yang; Yonghao Zhang; Yu Yao; Gang Pei; Hua Tian; Lingfeng Shi; Gequn Shu (Science Bulletin, 2025)

Improving the efficiency of a CO2 heat pump for simultaneous heating and cooling coupled with an ambient source - Zhaoyang Yuan; Jintao He; Yonghao Zhang; Yu Yao; Hua Tian; Lingfeng Shi; Gequn Shu (International Journal of Refrigeration, 2025)

Effect of annealing and tea polyphenols on the physicochemical properties of mango starch - Rui Huang; Yaqin Yu; Mengzhu Shen; Lingfeng Cheng; Yitong Chen; Hongwei Wu; Fangfang Wu; Chao Huang; Yong Hu; Yun Chen (Food Bioscience, 2025)

A hybrid cooling and power cogeneration scheme for broadening adaptability to distributed buildings: conceptual design, modeling, and operational assessment - Yonghao Zhang; Lingfeng Shi; Hua Tian; Jintao He; Yu Yao; Gequn Shu (Energy and Buildings, 2025)

Shell Colour Diversity in Marine Molluscs: From Current Knowledge to Future Aquaculture Applications - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Qi Li (Reviews in Aquaculture, 2025)
Mollusc shell colour represents an important economic trait contributing to product marketability in aquaculture. Marine molluscs with diverse shell colours and patterns are valuable models for animal colouration mechanisms study. Recent progress in marine mollusc shell colour research has been propelled by investigations of shell‐colour variants, advancements in high‐throughput sequencing technologies, and research into metabolic regulatory mechanisms for pigment biosynthesis. This review synthesizes current advancements in genetic architecture, gene regulatory networks and pigment metabolic processes governing shell colour variation in marine molluscs. In this review, insights gained from genetic studies uncover diverse inheritance patterns, key loci and present shell‐colour‐related transcriptomic datasets along with integrative multi‐omics studies. Moreover, distribution, metabolic networks and functional gene linkages of major pigments (melanin, carotenoids, and porphyrins) are characterized, while ommochromes are also discussed. Furthermore, environmental, dietary and structural factors influencing shell colour are listed. By synthesizing current findings, this review offers a detailed overview of the common factors influencing shell colour across marine mollusc species and probes the potential implications of shell colour studies for aquaculture. Future research directions emphasize pigment characterization, pigment transport mechanism studies and integrative multi‐omics approaches to bridge genetic and chemical understandings. In summary, this review outlines the current progress on marine mollusc shell colouration, provides referable research directions on shell‐colour‐related molluscs, and enhances understanding of animal colouration mechanisms.

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Adaptive Responses in Byssal Growth and Shedding: Insights from Pteria penguin Under Thread Trimming and Non-Trimming Conditions - Hebert Ely Vasquez; Shangkun Wei; Guoliang Yang; Lingfeng Wang; Peixuan Yu; Mingyue Dong; Chao Yuan; Xing Zheng (Journal of Marine Science and Engineering, 2025)
Bivalves use byssal threads for attachment and locomotion, periodically shedding and regenerating them. In the winged pearl oyster Pteria penguin—known for its strong byssus and its role in the pearl industry—shedding may occur when the byssal stalk reaches a critical size, although the underlying mechanism remains unclear. This study investigated whether artificial manipulation of the byssus (via trimming) could stimulate thread production and promote shedding in adult P. penguin from two size groups. Byssal threads attached to the substrate were trimmed every 3–5 days over a 30-day period and compared to untrimmed controls. Oysters with trimmed byssus produced significantly more threads, with smaller individuals outperforming larger ones in both thread count and byssal stalk diameter. Moreover, small oysters exhibited a higher frequency of complete byssal shedding. These findings suggest that trimming stimulates thread production and accelerates stalk thickening, potentially triggering shedding due to spatial constraints at the attachment site. This response appears to reflect an adaptive mechanism for maintaining effective attachment and may help explain how mechanical or environmental cues influence byssal dynamics. Understanding this process offers new insight into the behavioral and physiological plasticity of P. penguin, with potential applications in pearl oyster management and aquaculture.

DOPA Decarboxylase (DDC) in Pacific Oysters: Characterization and Role in Tyrosine Metabolism and Melanogenesis - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

CgPPOX and CgFECH Mediate Protoporphyrin IX Accumulation Predominantly in the Outer Mantle Fold of Pacific Oyster Crassostrea gigas - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

DNA Methylation of Somatic Tissues in Oysters is Influenced by Sex and Heredity - Wen Teng; Chengxun Xu; Shikai Liu; Hong Yu; Lingfeng Kong; Qi Li (Marine Biotechnology, 2025)

Examination of the roles of CgTH in tyrosine metabolism and pigmentation of Pacific oyster (Crassostrea gigas) - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Aquaculture, 2025)

Bioorthogonal surface-edited exosomes for targeted multimodal imaging and synergic chemophototherapy of oral cancer - Yuxiao Wu; Xiaofeng Shan; Yuanjie Zhang; Wen Shi; Xingxing Zhu; Mengfan Yu; Shang Xie; Lingfeng Guo; Zhiqian Chen; Chuanling Zhang; Demin Zhou; Zhigang Cai (Chemical Engineering Journal, 2024)

Characterization of piRNAs in Diploid and Triploid Pacific Oyster Gonads: Exploring Their Potential Roles in Triploid Sterility - Yaru Zhou; Hong Yu; Qi Li; Lingfeng Kong; Shikai Liu; Chengxun Xu (Marine Biotechnology, 2024)

Comparative analysis on growth performance, survival and harvest traits between offspring from wild and mass-selected populations of Crassostrea nippona - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Aquaculture, 2024)

OysterDB: A Genome Database for Ostreidae - Xinchun Li; Yitian Bai; Chengxun Xu; Shikai Liu; Hong Yu; Lingfeng Kong; Shaojun Du; Qi Li (Marine Biotechnology, 2024)

Dietary Supplementation of β-Carotene Reveals miRNAs Involved in the Regulation of Carotenoid Metabolism in Crassostrea gigas - Dongfang Sun; Sai Wan; Hong Yu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2024)

Examination of the effects of impaired spermatogenesis on sterility in triploid oysters (Crassostrea gigas), and implications for commercial aquaculture - Chen Chen; Hong Yu; Qi Li; Lingfeng Kong; Shikai Liu; Chengxun Xu (Aquaculture, 2024)

Cation-driven self-assembly of core–shell covalent organic frameworks@Ti3CN MXene nanospheres for high-performance aqueous zinc-ion hybrid supercapacitors - Kaige Zhang; Quan Zong; Kuixing Ding; Ying Wang; Lingfeng Gao; Dongdong Xu; Zhonghui Chen; Huanan Yu (Chemical Engineering Journal, 2024)

cAMP-Mediated CREM-MITF-TYR Axis Regulates Melanin Synthesis in Pacific Oysters - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Physiological and transcriptomic analysis revealed that the accumulation of reactive oxygen species caused the low temperature sensitivity of Liriodendron × sinoamericanum - Ye Lu; Lingfeng Hu; Long Yu; Shuang Liang; Haoxian Qu; Mingqi Wang; Zhaodong Hao; Liming Yang; Jisen Shi; Jinhui Chen (Plant Science, 2024)

Transcriptomic and Physiological Analysis Reveal Melanin Synthesis-Related Genes and Pathways in Pacific Oysters (Crassostrea gigas) - Kunyin Jiang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Prediction of debris flow blocking river hazard chain by the numerical simulation: the Cutou catchment, Wenchuan County, China - Xianzheng Zhang; Yongbo Tie; Chenxiao Tang; Yajie Yu; Lingfeng Gong; Jiang Xiong (Bulletin of Engineering Geology and the Environment, 2024)

Genetic improvement of oysters: Current status, challenges, and prospects - Kunyin Jiang; Chen Chen; Gaowei Jiang; Yong Chi; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Reviews in Aquaculture, 2024)
Oysters are one of the most commercially important shellfish species and have been cultured for thousands of years. Oyster aquaculture supports the major aquaculture industries in many countries. Over the last few decades, the oyster breeding and aquaculture industries have developed rapidly to meet the continually growing demand. Many researchers have made significant efforts toward the genetic improvement of commercially important traits in oysters. Some strains with fast‐growing, disease‐resistant, and stable shell‐colours have been developed through selective breeding. Some hybrid varieties have been developed by crossing different geographical populations or cultivated strains. Several hybrids exhibit considerable genetic variation and improved productive performance. Additionally, polyploid induction technologies have been applied in the oyster aquaculture industry, which provides a useful tool for performance improvement and genetic containment of cultured stocks. At present, the development of molecular breeding also provides a great opportunity for oyster genetic improvement. These advances in oyster breeding have improved the quality of oysters, brought great economic benefits, and been conducive to the sustainability of oyster production. Nonetheless, there are still some limitations and obstacles in oyster breeding, such as infectious diseases, summer mortality, conservation of germplasm resources, environmental contamination, and climate change. The present review provides an overview of the current status, challenges, and prospects in oyster breeding.

Growth patterns and optimum habitat of Larimichthys crocea throughout ontogenesis based on a bioenergetics model - Bin Xie; Shin-ichi Ito; Lingfeng Huang; Haiqing Yu; Chenying Guo; Ziqin Wang (Regional Studies in Marine Science, 2024)

More than just pandas: Urgent research needed on China's native plant biodiversity - Yu-heng Chen; Yao Li; Yu-ran Dong; Min Zhang; Yong Yang; Richard B. Primack; Kathryn E. Barry; Lingfeng Mao (Biological Conservation, 2024)

Revealing the specificity of map method to predict the performance of a combined cooling and power cycle under operating conditions - Yu Yao; Lingfeng Shi; Jintao He; Xiaocun Sun; Bowen Lu; Yonghao Zhang; Hua Tian; Xuan Wang; Gequn Shu (Journal of Cleaner Production, 2023)

Contraction of Heat Shock Protein 70 Genes Uncovers Heat Adaptability of Ostrea denselamellosa - Zhen Dong; Shikai Liu; Hong Yu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2023)

Future changes in hydrological drought across the Yangtze River Basin: identification, spatial–temporal characteristics, and concurrent probability - Jiarui Yu; Lei Zou; Jun Xia; Ming Dou; Huan Liu; Lingfeng Zuo (Journal of Hydrology, 2023)

Parallel evolution in Crassostrea oysters along the latitudinal gradient is associated with variation in multiple genes involved in adipogenesis - Wen Teng; Huiru Fu; Zhuanzhuan Li; Qian Zhang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Molecular Ecology, 2023)
Parallel diversification provides a proper framework for studying the role of natural selection in evolution. Yet, empirical studies from ecological ‘non‐model’ species of invertebrates are limited at the whole genome level. Here, we presented a chromosome‐scale genome assembly for Crassostrea angulata and investigated the parallel genomic evolution in oysters. Specifically, we used population genomics approaches to compare two southern–northern oyster species pairs ( C . angulata – C . gigas and southern–northern C . ariakensis ) along the coast of China. The estimated divergence time of C . angulata and C . gigas is earlier than that of southern and northern C . ariakensis , which aligns with the overall elevated genome‐wide divergence. However, the southern–northern C . ariakensis F ST profile represented more extremely divergent “islands”. Combined with recent reciprocal hybridization studies, we proposed that they are currently at an early stage of speciation. These two southern–northern oyster species pairs exhibited significant repeatability in patterns of genome‐wide differentiation, especially in genomic regions with extremely high and low divergence. This suggested that divergent and purifying selection has contributed to the genomic parallelism between southern and northern latitudes. Top differentiated genomic regions shared in these two oyster species pairs contained candidate genes enriched for functions in energy metabolism, especially adipogenesis, which are closely related to reproductive behaviours. These genes might be good candidates for further investigation in vivo. In conclusion, our results suggest that similar divergent selection and shared genomic features could predictably transform standing genetic variation within one species pair into differences in another.

Storage allocation rules to meet shared water demands for optimal operation of reservoir water supply - Fang Wan; Yu Wang; Lingfeng Xiao; Qihui Chai (Irrigation and Drainage, 2023)
The priority principle of storage allocation rules of serial cascade reservoirs within an interbasin water supply can reduce water loss and reduce water supply times. Reasonable balancing curves for reservoirs in parallel are proposed, and the proportional distribution of water is determined to illustrate the optimal allocation rule for different reservoir scheduling periods. The mutation point and slope are used to describe the segmentation of reservoirs in parallel. Finally, the relative optimal water supply rule is obtained. Taking the reservoir groups in the lower reaches of the Luanhe River basin as the research object, the results show that the water supply obtained by the balancing curve is increased by approximately 4% compared with the compensation regulation, and wasted water is reduced by 10%. The results are close to the largest water supply, the annual average wasted water and the guarantee rate obtained by dynamic programming. The suggested method can achieve the operation goal effectively and improve the operation performance of the shared water demands for the reservoir water supply. This article highlights the superior results obtained compared with the current storage allocation rules to meet shared water demands.

Construction of hybridization chain reaction induced optical signal directed change of photonic crystals-DNA hydrogel sensor and its visual determination for aflatoxin B1 - Qianshan Chen; Lingfeng Wu; Feng Zhao; Bing Liu; Zhaoyang Wu; Ruqin Yu (Food Chemistry, 2023)

Effects of Dietary Cystine and Tyrosine Supplementation on Melanin Synthesis in the Pacific Oyster (Crassostrea gigas) - Zhuanzhuan Li; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Mitogenomic phylogeny of Muricidae (Gastropoda: Neogastropoda) - Yi Yu; Lingfeng Kong; Qi Li (Zoologica Scripta, 2023)
Muricidae is one of the most species‐rich and morphologically diverse families in Gastropoda, with a worldwide distribution. The classification of Muricidae has traditionally been based on shell and radular characteristics; however, the phylogenetic relationships within the family are debated due to morphological convergence and plasticity. In this study, to explore the phylogenetic relationships of Muricidae, we sequenced 11 muricid mitochondrial (mt) genomes and compared them with 13 previously reported complete muricid mt genomes. All muricid mt genomes shared the same gene arrangement and exhibited conserved genome size and nucleotide composition. Three‐nucleotide deletions in atp8 and nad4 , and three‐nucleotide insertions in nad2 were detected in Rapaninae. Both maximum likelihood and Bayesian inference analyses supported the monophyly of each subfamily studied (Ocenebrinae, Muricinae, Rapaninae and Ergalataxinae). Ergalataxinae was recovered as the sister taxon of Rapaninae, refuting the traditional morphology‐based placement of Ergalataxinae within Rapaninae. In Rapaninae, Indothais was confirmed to be monophyletic and determined to be a valid genus. Similarly, Drupina was determined to be an independent genus rather than a subgenus of Drupa . Purpura was recovered as a paraphyletic group, with Purpura panama being sister to Reishia + Rapana + Indothais and clustering with Purpura bufo .

Phylogenomic resolution of Imparidentia (Mollusca: Bivalvia) diversification through mitochondrial genomes - Yu Wang; Yi Yang; Lingfeng Kong; Takenori Sasaki; Qi Li (Marine Life Science & Technology, 2023)
Despite significant advances in the phylogenomics of bivalves over the past decade, the higher-level phylogeny of Imparidentia (a superorder of Heterodonta) remains elusive. Here, a total of five new mitochondrial sequences ( Chama asperella , Chama limbula , Chama dunkeri , Barnea manilensis and Ctena divergens ) was added to provide resolution in nodes that required additional study . Although the monophyly of Lucinida remains less clear, the results revealed the overall backbone of the Imparidentia tree and the monophyly of Imparidentia. Likewise, most relationships among the five major Imparidentia lineages—Lucinida, Cardiida, Adapedonta, Myida and Venerida—were addressed with a well-supported topology. Basal relationships of Imparidentia recovered Lucinidae as the sister group to all remaining imparidentian taxa. Thyasiridae is a sister group to other imparidentian bivalves (except Lucinidae species) which is split into Cardiida, Adapedonta and the divergent clade of Neoheterodontei. Neoheterodontei was comprised of Venerida and Myida, the former of which now also contains Chamidae as the sister group to all the remaining venerid taxa. Moreover, molecular divergence times were inferred by calibrating nine nodes in the Imparidentia tree of life by extinct taxa. The origin of these major clades ranged from Ordovician to Permian with the diversification through the Palaeozoic to Mesozoic. Overall, the results obtained in this study demonstrate a better-resolved Imparidentia phylogeny based on mitochondrial genomes.

Investigating the spatial–temporal changes of flood events across the Yangtze River Basin, China: Identification, spatial heterogeneity, and dominant impact factors - Jiarui Yu; Lei Zou; Jun Xia; Yongyong Zhang; Lingfeng Zuo; Xiaoyang Li (Journal of Hydrology, 2023)

Transcriptome Analysis of Reciprocal Hybrids Between Crassostrea gigas and C. angulata Reveals the Potential Mechanisms Underlying Thermo-Resistant Heterosis - Gaowei Jiang; Yin Li; Geng Cheng; Kunyin Jiang; Jianmin Zhou; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

A Comparative Study on the Difference in Temperature and Salinity Tolerance of Crassostrea nippona and C. gigas Spat - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Journal of Marine Science and Engineering, 2023)
Although Crassostrea nippona and C. gigas are occasionally found to be sympatric, little is known about the differences in tolerance against environmental stresses between species, which may potentially result in severe economic losses due to the neglect of species-specific biological characteristics in farming practices. Therefore, two independent and consecutive experiments were performed to evaluate the differences in temperature and salinity tolerance between C. nippona and C. gigas spat and determine the optimal environmental conditions for the aquaculture of C. nippona spat. The experimental results of dynamic treatment showed that the accumulative survival rate (ASR) of C. nippona spat was generally lower than that of C. gigas throughout temperature changes and salinity decreases, while the ASR of C. nippona spat was superior to that of C. gigas with increasing salinity. In addition, the daily growth rate (DGR) of both species was significantly inhibited at 18 °C and peaked at 25 °C with increasing temperature (p

Effect of Angiogenesis in Bone Tissue Engineering - Jianhao Huang; Qixiu Han; Meng Cai; Jie Zhu; Lan Li; Lingfeng Yu; Zhen Wang; Gentao Fan; Yan Zhu; Jingwei Lu; Guangxin Zhou (Annals of Biomedical Engineering, 2022)

The Clam Cyclina sinensis (Gmelin) Phylogeography Study with 28S rRNA Gene and Potential of Nuclear rRNA Genes in Genetic Assessments of Molluscs - Gang Ni; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2022)

Shell Biosynthesis and Pigmentation as Revealed by the Expression of Tyrosinase and Tyrosinase-like Protein Genes in Pacific Oyster (Crassostrea gigas) with Different Shell Colors - Yijing Zhu; Qi Li; Hong Yu; Shikai Liu; Lingfeng Kong (Marine Biotechnology, 2021)

Integrated Analysis of Coding Genes and Non-coding RNAs Associated with Shell Color in the Pacific Oyster (Crassostrea gigas) - Zhuanzhuan Li; Qi Li; Shikai Liu; Ziqiang Han; Lingfeng Kong; Hong Yu (Marine Biotechnology, 2021)

Phylogeny of Veneridae (Bivalvia) based on mitochondrial genomes - Yu Wang; Yi Yang; Hongyue Liu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Zoologica Scripta, 2021)
Veneridae is one of the most diverse families of bivalve molluscs. However, their phylogenetic relationships among subfamilies have been debated for years. To explore phylogenetic relationships of Veneridae, we sequenced 13 complete mitochondrial genome sequences from eight subfamilies and compared with available complete mitochondrial genome of other Veneridae taxa (18 previously reported sequences). Phylogenetic analyses using probabilistic methods recovered two highly supported clades. In addition, the protein‐coding gene order revealed a highly conserved pattern among the same subclade lineages. According to our molecular analyses, Tapetinae should be recognized as a valid subfamily, but the genera formed para‐polyphyletic clades. Chioninae was recovered not monophyletic that differs from a previously molecular phylogeny. Furthermore, the reconstructed chronogram calibrated with fossils recovered the Veneridae have originated during the early Permian (about 290 million years ago). Noticeably, programmed frameshift was found in the nad4 gene of Leukoma jedoensis , Anomalodiscus squamosus and Antigona lamellaris and cob gene of L. jedoensis . This is the first time that the presence of the programmed frameshift has been found in the protein‐coding genes of Heterodonta species. Our results improved the phylogenetic resolution within Veneridae, and a more taxonomic sampling analysis of the subfamily Chioninae is supposed to construct.

Mitogenomic phylogeny of Trochoidea (Gastropoda: Vetigastropoda): New insights from increased complete genomes - Erfei Guo; Yi Yang; Lingfeng Kong; Hong Yu; Shikai Liu; Zhanjiang Liu; Qi Li (Zoologica Scripta, 2021)
Increased mitochondrial (mt) genomes can provide more sets of genome‐level characteristics for resolving deeper phylogeny. Limited information with respect to the Trochoidea mitochondrial genome organization is available; besides, monophyly and internal relationships of the superfamily still remain a matter of discussion. To resolve the monophyly and internal phylogenetic controversies of Trochoidea and expand our understanding for mt genomic characteristic evolution among Trochoidea, the phylogenetic trees were reconstructed using 13 newly sequenced complete mt genomes and 35 genomes from GenBank, and both the maximum likelihood and Bayesian inference analyses were highly supported. Vetigastropoda phylogenetic analyses recovered the monophyly of Trochoidea. Trochoidea phylogenetic analyses and genetic distances supported the non‐monophyly of Tegulidae and Tegula , indicating that the taxonomic status of several genera ( Rochia , Tectus and Cittarium ) should be revised and Tegula , Omphalius and Chlorostoma should be placed as a same genus. The close affinity between Tectus virgatus and Rochia was also revealed. Three‐nucleotide insertion in nad1 , nine‐nucleotide insertion and six‐nucleotide deletion in nad5 are detected in Tegulidae, Tectus and Rochia , respectively. Gene orders within Trochoidea are stable, with gene rearrangements exclusive to tRNA genes observed. Homoplasious convergences because of trnT rearrangement display translocation in Turbinidae and reversion in Trochidae and Calliostomatida. For trnE and trnG , we identify 11 arrangement types, suggesting that the gene rearrangement history needs to be further evaluated. Our study emphasizes the importance of mt genomes in resolving phylogenetic relationships within Trochoidea. In addition, the mt genomic characters would contribute new insights into the classification of Trochoidea.

Validation of Housekeeping Genes for Gene Expression Analysis in Iwagaki Oyster (Crassostrea nippona) Under Salinity Stress by Quantitative Real-Time PCR - Jianwen Gong; Qi Li; Hong Yu; Shikai Liu; Lingfeng Kong (Journal of Ocean University of China, 2020)

Fertilization, survival and growth of hybrids between Crassostrea gigas and Crassostrea sikamea - Hongqiang Xu; Qi Li; Lingfeng Kong; Hong Yu; Shikai Liu (Fisheries Science, 2019)

Mitogenomic phylogeny of Nassarius (Gastropoda: Neogastropoda) - Yi Yang; Qi Li; Lingfeng Kong; Hong Yu (Zoologica Scripta, 2019)
Nassariids (Family Nassariidae) are a group of marine snails that are distributed worldwide, with their maximum species diversity in tropical regions, particularly the Indo‐Pacific. However, the traditional taxonomy of Nassariidae defined by shell or radula characters is usually inconsistent with little phylogenetic signal. In the present study, the complete mitochondrial (mt) genomes of nine Nassarius species were sequenced and compared with other eight nassariid species previously reported. All nassariid mt genomes showed the same gene order as in most caenogastropods and shared a very similar pattern with respect to genome size, nucleotide composition and AT contents. A deletion of three nucleotides in nad6 gene was detected in Nassarius jacksonianus and Nassarius acuticostus , and this feature also provided implications for nassariid phylogeny. The genetic distance analysis and reconstructed phylogeny revealed a distant relationship between N . jacksonianus or N. acuticostus and other members in Nassarius . The mitogenomic phylogeny recovered the evolutionary relationships within Nassarius with high statistical support. In addition, a chronogram was reconstructed under an uncorrelated relaxed molecular clock, which dated the divergence among main lineages of Nassarius during ~31 MYA.

DNA methylation frequency and epigenetic variability of the Pacific oyster Crassostrea gigas in relation to the gametogenesis - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Fisheries Science, 2018)

The complete mitochondrial genome of Dosinia japonica (Bivalvia: Veneridae) - Changda Lv; Lingfeng Kong; Hong Yu; Qi Li (Conservation Genetics Resources, 2018)

Biochemical Composition and Nutritional Value of Different Shell Color Strains of Pacific Oyster Crassostrea gigas - Yijing Zhu; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2018)

Cryptic genetic diversity of Neverita didyma in the coast of China revealed by phylogeographic analysis: implications for management and conservation - Dan Zhao; Lingfeng Kong; Hong Yu; Qi Li (Conservation Genetics, 2018)

Epigenetic variation of wild populations of the Pacific oyster Crassostrea gigas determined by methylation-sensitive amplified polymorphism analysis - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Fisheries Science, 2018)

DNA methylation changes detected by methylation-sensitive amplified polymorphism in the Pacific oyster (Crassostrea gigas) in response to salinity stress - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Genes & Genomics, 2017)

Estimates of Heritability for Growth and Shell Color Traits and Their Genetic Correlations in the Black Shell Strain of Pacific Oyster Crassostrea gigas - Lan Xu; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2017)

Expression and DNA methylation pattern of reproduction-related genes in partially fertile triploid Pacific oysters Crassostrea gigas - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Genes & Genomics, 2017)

Complete mitochondrial genome sequence of Cucullaea labiata (Arcoida: Cucullaeidae) and phylogenetic implications - Yanwei Feng; Qi Li; Hong Yu; Lingfeng Kong (Genes & Genomics, 2017)

Comparison of microsatellites and SNPs for pedigree analysis in the Pacific oyster Crassostrea gigas - Ting Liu; Qi Li; Lingfeng Kong; Hong Yu (Aquaculture International, 2017)

Cryptic diversity of marine gastropod Monodonta labio (Trochidae): did the early Pleistocene glacial isolation and sea surface temperature gradient jointly drive diversification of sister species and/or subspecies in the Northwestern Pacific? - Dan Zhao; Qi Li; Lingfeng Kong; Hong Yu (Marine Ecology, 2017)
Formation of glacial refugia during the Pleistocene climatic oscillations has been put forward to elucidate the diversification of marine organisms in the north‐western Pacific. The marine gastropod Monodonta labio is one of the most common species in the Northwestern Pacific and possibly possesses cryptic diversity. Here, we investigate the phylogeographic pattern of this species to test the potential mechanisms driving its diversification in the Northwestern Pacific. Genetic information for two mitochondrial genes (Cytochrome oxidase subunit I and 16S rDNA) and one nuclear gene (internal transcribed spacer 1) was acquired to detect genetic structuring and to reconstruct the gastropod's phylogenetic history. Our results revealed that M. labio is comprised of five main clades, and divergence time estimates place their cladogenesis as corresponding to the initiation ( c . 2.5 mya) and intensification ( c . 0.9 mya) of large‐scale Northern Hemisphere ice sheets. The early and middle Pleistocene divergence times are consistent with the emergence times of the Dongshan land bridge, which would seperate the ancient East China Sea and the ancient South China Sea forming two potential refugia. In addition, the deep trough in the Qiongzhou Strait would possibly act as another potential refugium with the uplift of the Qiongzhou Strait at mid‐Pleistocene. This study suggests that the current genetic architecture of M. labio is probably correlated with glacial isolation and sea surface temperature gradient. We also put forward the possibility that these factors were probably an important driver for the diversification of sister species or subspecies of other taxa in the Northwestern Pacific.

Relationship between single nucleotide polymorphism of glycogen synthase gene of Pacific oyster Crassostrea gigas and its glycogen content - Siwei Liu; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2017)

Genetic variation assessed with microsatellites in mass selection lines of the Pacific oyster (Crassostrea gigas) in China - Xubo Wang; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2016)

Gene Co-Expression Network Analysis Reveals the Correlation Patterns Among Genes in Euryhaline Adaptation of Crassostrea gigas - Xuelin Zhao; Hong Yu; Lingfeng Kong; Qi Li (Marine Biotechnology, 2016)

Microsatellite-centromere mapping in Japanese scallop (Patinopecten yessoensis) through half-tetrad analysis in gynogenetic diploid families - Qi Li; Mingjun Qi; Hongtao Nie; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Linkage disequilibrium in wild and cultured populations of Pacific oyster (Crassostrea gigas) - Xiang Guo; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Development of three multiplex PCR primer sets for ark shell (Scapharca broughtonii) and their validation in parentage assignment - Ning Li; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Inheritance and Variation of Genomic DNA Methylation in Diploid and Triploid Pacific Oyster (Crassostrea gigas) - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2016)

Genetic variation and population structure of the Pacific oyster Crassostrea gigas in the northwestern Pacific inferred from mitochondrial COI sequences - Shuang Li; Qi Li; Hong Yu; Lingfeng Kong; Shikai Liu (Fisheries Science, 2015)

Identification of Single-Locus PCR-Based Markers Linked to Shell Background Color in the Pacific Oyster (Crassostrea gigas) - Jianlong Ge; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2015)

Utility of DNA Barcoding for Tellinoidea: A Comparison of Distance, Coalescent and Character-based Methods on Multiple Genes - Zhenzhen Yu; Qi Li; Lingfeng Kong; Hong Yu (Marine Biotechnology, 2015)

QTL mapping for glycogen content and shell pigmentation in the Pacific oyster Crassostrea gigas using microsatellites and SNPs - Xiaoxiao Zhong; Qi Li; Xiang Guo; Hong Yu; Lingfeng Kong (Aquaculture International, 2014)

Genome-Wide Analysis of Simple Sequence Repeats in Marine Animals—a Comparative Approach - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2014)

Molecular cloning and differential expression in tissues of a tyrosinase gene in the Pacific oyster Crassostrea gigas - Xue Yu; Hong Yu; Lingfeng Kong; Fengguang Guo; Guan Zhu; Qi Li (Molecular Biology Reports, 2014)

The effect of chemical cues on the settlement of sea cucumber (Apostichopus japonicus) larvae - Xiujun Sun; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2014)

Additional lines of evidence provide new insights into species diversity of the Paphia subgenus Protapes (Mollusca, Bivalvia, Veneridae) in seas of south China - Jun Chen; Qi Li; Lingfeng Kong; Xue Yu (Marine Biodiversity, 2014)

Comparative phylogeography in marginal seas of the northwestern Pacific - Gang Ni; QI Li; Lingfeng Kong; Hong Yu (Molecular Ecology, 2014)
The maturation of marine phylogeography depends on integration of comparative information across different regions globally. The northwestern Pacific, characterized by unique tectonic setting, however, is still underrepresented. This study seeks to highlight its phylogeographical history based on the available population data, focusing on three seas: the East China Sea ( ECS ), the South China Sea ( SCS ) and the Sea of Japan ( SOJ ). We first conducted a literature survey to evaluate current research efforts and then reanalysed the population structure, historical demography and genealogy for two selections of studies (namely ‘the ECS category’ and ‘the multiple‐sea category’) to elucidate the evolutionary processes within and across the seas, respectively. For the ECS category, the meta‐analyses revealed most studies displayed a shallow phylogeny, indicating a single origin from the sea. Significant population structure was commonplace, particularly in molluck and crustacean studies, with proportions of 89% and 80%, respectively. Nearly all studies selected showed signals of population expansion: the times estimated were closely linked to a period of ~120–140 Kya rather than the last glacial maximum. For the latter category, divergent intraspecific lineages appeared among seas and overlapped in the adjacent regions, a pattern implying each sea had served as an independent refugium during glaciations. The genetic splits, however, were estimated to arise from separate events dating from late Miocene to middle Pleistocene. As phylogeography is still in its infancy in the region, more effort is needed to test and complement the general rules abstracted here. Finally, challenges and prospects were discussed to accelerate further research.

Isolation and characterization of 23 microsatellite loci in the veined rapa whelk (Rapana venosa) - Junting An; Hong Yu; Ruihai Yu; Lingfeng Kong; Qi Li (Conservation Genetics Resources, 2013)

Isolation and characterization of 14 microsatellite loci in Macridiscus semicancellata (Koch in Philippi, 1843) - Xinyu Liu; Lingfeng Kong; Hong Yu; Qi Li (Conservation Genetics Resources, 2013)

Response to selection for fast growth in the second generation of Pacific oyster (Crassostrea gigas) - Qingzhi Wang; Qi Li; Lingfeng Kong; Ruihai Yu (Journal of Ocean University of China, 2012)

Isolation and characterization of 20 microsatellite loci in Neverita didyma (Röding 1798) - Ning Li; Qi Li; Minyu Jin; Lingfeng Kong; Hong Yu (Conservation Genetics Resources, 2012)

The complete mitochondrial genome of the grand jackknife clam, Solen grandis (Bivalvia: Solenidae): a novel gene order and unusual non-coding region - Yang Yuan; Qi Li; Lingfeng Kong; Hong Yu (Molecular Biology Reports, 2012)

Identification and characterization of 43 microsatellite markers derived from expressed sequence tags of the sea cucumber (Apostichopus japonicus) - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2011)

Velocity Variation Assessment of Red Blood Cell Aggregation with Spectral Domain Doppler Optical Coherence Tomography - Xiangqun Xu; Lingfeng Yu; Zhongping Chen (Annals of Biomedical Engineering, 2010)

Seasonal changes in reproductive activity and biochemical composition of the razor clam Sinonovacula constricta (Lamarck 1818) - Hongwei Yan; Qi Li; Wenguang Liu; Ruihai Yu; Lingfeng Kong (Marine Biology Research, 2010)

Seasonal variation of the glycogen enzyme activity in diploid and triploid Pacific oyster gonad during sexual maturation - Lingfeng Kong; Zhaoping Wang; Ruihai Yu; Qi Li; Rucai Wang (Journal of Ocean University of China, 2007)